(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
The rapid integration of digital technologies into higher education has significantly transformed learning processes, particularly for first-year university students. This study investigates the impact of digital learning environments on students’ self-learning abilities, focusing on self-regulation, autonomy, and independent learning skills. Using a mixed-method approach, data were collected from first-year students through surveys and semi-structured interviews. The findings reveal that digital learning environments positively influence students’ self-learning abilities by enhancing motivation, flexibility, and access to learning resources. However, challenges such as lack of self-discipline and digital literacy gaps were also identified. The study concludes that while digital platforms can effectively promote self-learning, structured guidance and support systems are essential for maximizing their benefits.